Comparative Transcriptome Analysis of the Regenerating Zebrafish Telencephalon Unravels a Resource With Key Pathways During Two Early Stages and Activation of Wnt/β-Catenin Signaling at the Early Wound Healing Stage - Demirci, Yeliz; Cucun, Gokhan; Poyraz, Yusuf Kaan; Mohammed, Suhaib; Heger, Guillaume; Papatheodorou, Irene; Ozhan, Gunes (Frontiers in Cell and Developmental Biology, 2020)
Owing to its pronounced regenerative capacity in many tissues and organs, the zebrafish brain represents an ideal platform to understand the endogenous regeneration mechanisms that restore tissue integrity and function upon injury or disease. Although radial glial and neuronal cell populations have been characterized with respect to specific marker genes, comprehensive transcriptomic profiling of the regenerating telencephalon has not been conducted so far. Here by processing the lesioned and unlesioned hemispheres of the telencephalon separately, we reveal the differentially expressed genes (DEGs) at early wound healing and early proliferative stages of regeneration, i.e. 20-hours post-lesion (hpl) and 3-days post-lesion (dpl), respectively. At 20 hpl, we detect a far higher number of DEGs in the lesioned hemisphere than in the unlesioned half and only 7% of all DEGs in both halves. However, this difference disappears at 3 dpl where the lesioned and unlesioned hemispheres share 40% of all DEGs. By performing an extensive comparison of gene expression profiles in these stages, we unravel that the lesioned hemispheres at 20 hpl and 3 dpl exhibit distinct transcriptional profiles. We further unveil a prominent activation of Wnt/β-catenin signaling at 20 hpl, returning to control level in the lesioned site at 3 dpl. Wnt/β-catenin signaling indeed appears to control a large number of genes associated primarily with p53, apoptosis, FoxO, MAPK and mTOR signaling pathways specifically at 20 hpl. Based on these results, we propose that the lesioned and unlesioned hemispheres react to injury dynamically during telencephalon regeneration and that activation of Wnt/β-catenin signaling at early wound healing stage plays a key role in regulation of cellular and molecular events.